ADSORPSI LOGAM KADMIUM (Cd) OLEH ARANG AKTIF DARI TEMPURUNG AREN (Arenga pinnata) DENGAN AKTIVATOR HCl - Indri Ayu Lestari; Alimuddin -; Bohari Yusuf (JURNAL KIMIA MULAWARMAN, 2014)
The adsorption of cadmium (Cd2+) by palm shell carbon (Arenga pinnata) activated carbon have been researched. This research is aim to find the effects of pH value, contact time and concentration. In this research, the variations of pH value was (2 – 7), contact time (5 – 70 minutes) and concentration (1,5 – 3,5 mg/L) were applied. The determination of cadmium concentration used an Atomic Absorption Spectrophotometer (AAS). The result of this research shows that pal shell activated carbon could adsorp metal ion Cd 2+ . The optimum condition was achieved at the pH 3 with a capacity factor of adsorbent was 2,372 mg/L or 94,92%, contact time was 30 minutes with a capacity factor of adsorbent was 2,327 mg/L or 93,12% and concentration was achieved at the concentration 3,5 mg/L with a capacity factor of adsorbent was 3,321 mg/L or 94,91%.Keywords: adsorption, actived carbon, palm shell, metal ions Cd 2+